Cisplatin Induce Changes of Cell Surface Glycoconjugates in Germinal Epithelium of Seminiferous Tubules - Mohammad Rigi Manesh; Mohammad Reza Arab; Fereydoon Sargolzaei Aval; Mohamad Ali Mashhadi; Narjes Sargolzaei; Mohsen Mir; Masoud Shahraki Salar (Negah Institute for Scientific Communication, 2018)
Introduction: Cisplatin is a platinum-based drug widely used for the treatment of different cancers. Cell surface glycoconjugates play an important role in cell-cell interactions. The present investigation was carried out to study the toxic effects of double dose injection of cisplatin on cell surface glycoconjugates in rat as an experimental model. Methods: In this experimental study, 45 adult male Sprague Dawley rats were used. Experimental group E1 and experimental group E2 received two repeated dose of 2.5 mg/kg and 5 mg/kg of cisplatin, respectively in the beginning of the first and fifth week of the experiment. After 8 weeks of injection, rats were killed. Tissue samples were removed and prepared sections were stained with H&E, PNA (Peanut agglutinin), and UEA (Ulex europaeus agglutinin) methods. Prepared microscopic slides were utilized for both histopathological and morphometrical studies. The obtained data were analyzed by ANOVA and Tukey tests using SPSS. Results: Cisplatin administration induced a significant decrease in internal and external diameters of seminiferous tubules in the experimental groups compared to the control one (P<0.0001). There was also significant difference between control and experimental groups with regard to germinal epithelial thickness of seminiferous tubules (P<0.0001). Moreover, there was a significant difference between control and experimental groups with regard to spermatogenesis index (P<0.004). Also a significant elevation was seen in staining intensity of germinal epithelium to PNA and UEA in experimental groups, compared to control group (P<0.0001). Conclusion: Cisplatin induces a dose-dependent morphological changes of germinal epithelium and extensive changes in distribution pattern of fucose- and Gal/GalNac-containing glycoconjugates in seminiferous epithelium in rats.